Analysis of the books “White Fang” and “Colmillo Blanco” in an attempt to determine how Motion Verbs differ in English and Spanish based on Leonard Talmy’s approach to Cognitive Analysis of Motion Verbs. - Vélez Vera, Jimmy Andrés (2016)
The Project describes and explains the characteristics of Motion Verbs in Spanish and English established by Talmy (1985, 1991, 2000) in order to help translators to convey these characteristics in a proper way. The first part of the Project includes a brief description of other approaches in the field, as well as, a study made by Naigles, Eisenberg, Kako, Highter & McGraw (1998), which examined the differences on the way adult English and Spanish speakers produce static and dynamic Motion Events in their respective language. The second part of it contains a well-detailed explanation (including examples) of each of the components of a Motion Verb established by Talmy (1985, 1991, 2000), a definition of the most relevant words included in the Project and an exhaustive analysis of the translation of Motion Verbs from the book “White Fang” and its equivalent in Spanish, “Colmillo Blanco”. Additionally, Translation Strategies particularly focusing on Path and Manner information, as well as, an analysis of the Linguistic Devices (Translation Techniques) used in the translation of “White Fang” into “Colmillo Blanco” has been included.